Quality profile of ginger under different management systems - N K Leela, C K Thankamani, C R Nileena, V Srinivasan, S Hamza, (Journal of Spices and Aromatic Crops, 2014)
Field experiments were conducted to find out the variation in yield, and quality profile of ginger under organic, inorganic and integrated management systems for three consecutive years (2007–2009). Ginger varieties, IISR Varada, IISR Mahima and IISR Rejatha were used for the experiment. Results showed that among the treatments, the yield was on par in organic and integrated management system. The oil content was significantly higher in integrated and inorganic management systems and oleoresin in inorganic system. The essential oil constituents viz., zingiberene, farnesene, α-pinene, citral, 1, 8 cineole, z-citral and camphene contents were highest in integrated management system. β-Sesquiphellandrene content was highest under inorganic management and ar-curcumene content was highest under organic management system. Among the three varieties, IISR Mahima recorded significantly higher yield, oleoresin, β-Sesquiphellandrene and ar-curcumene contents. In the case of oil and zingiberene content, there was no significant difference among the varieties. IISR Varada recorded maximum oleoresin, α-pinene, citral, 1,8 cineole, z-citral and camphene content while IISR Rejatha recorded the highest farnesene and ar-curcumene content.